2010
DOI: 10.1016/j.cell.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Second Messenger-Mediated Adjustment of Bacterial Swimming Velocity

Abstract: Bacteria swim by means of rotating flagella that are powered by ion influx through membrane-spanning motor complexes. Escherichia coli and related species harness a chemosensory and signal transduction machinery that governs the direction of flagellar rotation and allows them to navigate in chemical gradients. Here, we show that Escherichia coli can also fine-tune its swimming speed with the help of a molecular brake (YcgR) that, upon binding of the nucleotide second messenger cyclic di-GMP, interacts with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
475
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(494 citation statements)
references
References 53 publications
15
475
1
3
Order By: Relevance
“…Moreover, CsgD modulates adrA upregulation, which encodes one of the enzymes for cyclic di-GMP synthesis (Ogasawara et al, 2010). c-di-GMP consequently inhibits cell motility by interfering with the flagella motor speed via the c-di-GMP-binding protein YcgR (Wolfe and Visick, 2008;Boehm et al, 2010). From our results, we can suggest that Saci0446 acts in a rather opposite manner when compared with CsgD from E. coli, as Saci0446 activates archaella synthesis and represses genes required for biofilm formation.…”
Section: Regulation Of Crenarchaeal Biofilm Formationmentioning
confidence: 56%
“…Moreover, CsgD modulates adrA upregulation, which encodes one of the enzymes for cyclic di-GMP synthesis (Ogasawara et al, 2010). c-di-GMP consequently inhibits cell motility by interfering with the flagella motor speed via the c-di-GMP-binding protein YcgR (Wolfe and Visick, 2008;Boehm et al, 2010). From our results, we can suggest that Saci0446 acts in a rather opposite manner when compared with CsgD from E. coli, as Saci0446 activates archaella synthesis and represses genes required for biofilm formation.…”
Section: Regulation Of Crenarchaeal Biofilm Formationmentioning
confidence: 56%
“…The applicability of DRa-CALA to high-throughput metabolite interactomics was demonstrated by screening for binding proteins of an important secondary signaling dinucleotide, cdiGMP. Recent findings have identified cdiGMP as the signaling molecule that controls biofilm formation, motility, and a number of other bacterial functions (2,3,(25)(26)(27). Although the enzymes known to synthesize and degrade cdiGMP are restricted to bacteria, there are questions as to which bacterial species express cdiGMP-binding proteins.…”
Section: Dracala Detection Of Cdigmp-binding Proteins In Diverse Pro-mentioning
confidence: 99%
“…The switching probability increases linearly with increase in motor torque in both directions, suggesting that the switch senses the load on the stator-rotor interaction as well as the level of CheY-P (18). Recently, it has been reported that the c-di-GMP binding protein YcgR binds to MotA, FliG, and FliM in the presence of c-di-GMP, resulting not only in a reduced motor speed but also in the CCW bias in motor rotation (3,4). In Rhodobacter sphaeroides, the flagellar motor rotation is unidirectional, but CheY-P acts as a molecular brake to stop motor rotation to change the swimming direction (19).…”
mentioning
confidence: 99%
“…Such behavior is called taxis, which involves sensory reception, signal transduction, and the modulation of the motor function (1). Bacterial motility is also controlled by an intracellular signalling molecule, c-di-GMP, to facilitate biofilm formation, which often causes serious troubles in human life (2)(3)(4). Thus, bacterial motility and behavior are fundamental properties for their life cycle, and hence it is of eminent importance to understand their basic mechanisms for the welfare of human society.…”
mentioning
confidence: 99%